The Variety of Local food diets in Lower Mekong sub-region Community of Thailand and Lao PDR - Suwaree Sripoona, Kanittha Pamonpol, Prapasri Termsaithong, Kobkhan Gubtapol, Prasert Laobusnanant (International Journal of Advanced Science and Technology, 2020)
Sustainable diets and biodiversity were proposed since early 1980s in order to have better environments and healthier consumers. FAO reported billion poor people suffer from hunger and malnutrition, while rich people suffer from overweight or obese. Food ingredient provides link for biodiversity and nutrition. Ingredients of food are various in each area. Although in the same country but different areas food is not the same because of availability of natural resources. The local food in Lower Mekong sub-region Community of Thailand and Lao PDR was unique. This research aims at conserve traditional knowledge of local food and wild food biodiversity for nutrition security and health outcome. The studied site was at Chiangkhan District, Loei Province, Thailand and Chanakam, Vientiane City, Lao PDR. The nutrient of local food was analyzed. The results found that there was diversity of local food for more than 100 recipes. Both Thai and Laos had similar food because they were located in the same area that could find raw materials from wild herbs and animals in Mekong River and nearby. Each set of food had ratio of vegetable to protein for 7:3 and one deck contained 2-3 recipes. Most ingredients were herbs such as chili, lemongrass, galangal, onion in every recipe. Nutrient analysis of local food found high amount of calcium, vitamin A, and vitamin C, but low amount of fat. Therefore, the local food was useful for bone, heart, sight, skin, strength of red blood cell wall, eyes and not broken easily and immune to disease. The food was available more in rainy season because there was various biodiversity.